Studying chemical transformations of the modified derma collagen - Zhaldak, Maryna; Mokrousova, Olena (Eastern-European Journal of Enterprise Technologies, 2019)
Chemical transformations of modified collagen for prediction of effective formation and stabilization of the derma structure with the use of montmorillonite dispersions treated by different modifying agents were studied. Identification of chemical interactions was estimated using infrared spectroscopic studies on gelatin, amino acid composition of which is close to collagen. The existence of active in interaction carboxylic, amino-, peptide and hydrogen groups in the collagen structure contributes to effective structuring of derma. During processing of skins into leather, the transformation of bonds in collagen occurs. In this case, chemical materials interact with the functional groups of protein and form new chemical bonds. This contributes to stabilization of the structure of derma. This results in the formation of a capillary-porous structure with the required level of operational and hygienic properties of leather. IR spectroscopic analysis revealed effective physical and chemical interactions between collagen and modified montmorillonite dispersions. This is proved by the formation of numerous bonds involving functional groups of gelatin and active centers of the mineral. The biggest changes are observed in high-frequency and low-frequency regions. Accordingly, the spectra characterize valence fluctuations involved in the formation of hydrogen, ionic and covalent bonds. This allows claiming that pre-chromed gelatin subsequently treated with aluminum-modified montmorillonite dispersion has more coordination bonds. This is caused by the hydroxo-complex ions of Cr (ІІІ) and Al (ІІІ), which are located between the silicate layers. At the same time, the presence of pre-chromed gelatin ensures the formation of additional intermolecular bonds, which can influence the stability of properties and structuring of derma collagen. Thus, there are grounds to argue about the possibility of more efficient use of chromium compounds during the tanning process. Due to the introduction of the composition based of montmorillonite modified by aluminum compounds, a decrease in consumption of chromium compounds will be achieved. This will make it possible to solve the problem of making production ecologically friendly and to enhance safety of leather for children’s footwear.